The Role of Social Media Use in Peer Bullying Victimization and Onset of Anxiety Among Indonesian Elementary School Children - Kaloeti, Dian Veronika Sakti; Manalu, Rouli; Kristiana, Ika Febrian; Bidzan, Mariola (Frontiers in Psychology, 2021)
Objectives: This study explored a multidimensional model of the relationships between social media use, gender, peer bullying victimization experiences, and the onset of anxiety symptoms among children. We hypothesized that higher bullying experiences would be associated with higher onset of anxiety. We also expected that gender and social media use (specifically Instagram and YouTube) would be linked with anxiety among elementary school children. To test this hypothesis, a structural equation modeling approach was used. Methods: A total of 456 elementary children aged 11–13 years from nine schools were recruited for this research. We used two psychological measures: The Screen for Child Anxiety Related Emotional Disorders (SCARED) and the Personal Experience Checklist (PECK) as well as a socio-demographic questionnaire (general demographic information and social media-related information). Results: The social media usage survey found that all participants (100%) used social media. Instagram (52.42%) and YouTube (47.58%) were the platforms most used by the participants. The Structural Equation Model results suggest that bullying victimization and gender predict the onset of anxiety in elementary school children. The model explained 32.1% of the variance of the outcome with very adequate fit indicators based on most indices, χ2 = 173.56, d.f = 52, p < .001; CFI = 0.92; TLI = 0.94; RMSEA = 0.07 (90% CI: 0.06–0.08). Instagram use was correlated positively with Generalized Anxiety Disorder. Being girls correlated with more Instagram use and being boys correlated with more YouTube use. Girls are more prone to the onset of anxiety than boys, except for school avoidance which is not related to gender. Boys were found to experience significantly more physical bullying than girls. On the other hand, girls were found to experience more Panic Disorder, Generalized Anxiety Disorder, Separation Anxiety Disorder, and Social Anxiety than boys. Conclusion: The findings of this study indicate that the victimization of bullying significantly influences the onset of anxiety in children, particularly cyberbullying. This study also found a link between gender and anxiety. Gender also correlates with the form of bullying victimization. Further, using Instagram was significantly correlated with developing separation anxiety. Limitations and future directions are discussed.